THE EFFECTS OF FATIGUE ON SCAPULA KINEMATICS DURING THROWING IN ELITE TEAM HANDBALL PLAYERS; DOES PAIN INFLUENCE? A PRELIMINARY STUDY. Issue 4 (1st February 2017) - Torabi, Tina Piil; Juul-Kristensen, Birgit; Dam, Mogens; Andersen, Frederik H.; Malchow-Møller, Lasse; Zebis, Mette K; Møller, Merete; Bencke, Jesper
Abstract : Background: Non-traumatic shoulder injuries are common in overhead sports, however many athletes still participate in their sport despite pain. Non-optimal scapula kinematics at the instant of maximal humeral external rotation (HumExtRot) is considered a risk factor in overhead throwing sports. Objective: The aim of the study was to investigate whether a functional fatigue protocol affects scapula kinematics during throwing, and whether this effect is different between players who are pain-free and participating with pain. Design: A controlled intervention study. Setting: 3D Motion Analysis Laboratory with 8 cameras (Vicon T40, Oxford, UK). Patients (or Participants): 16 adult, mean age 21, 9(2, 4) years, elite female team handball players were recruited from top 2 leagues in Denmark. The participants were divided into two groups; 8 subjects playing with pain(P) and 8 subjects playing without pain(NP) served as controls. Interventions (or Assessment of Risk Factors): Measurements of scapula and gleno-humeral kinematics were collected during maximal throws before and after a fatiguing protocol, containing 60 alternated submaximal-and maximal throws. Main Outcome Measurements: Maximal HumExtRot in relation to scapula, scapula posterior tilt (ScapPostTilt), scapula retraction (ScapRetr) and scapula upward rotation (ScapUpRot) at the instant of maximal HumExtRot were selected as outcome parameters. Overall effects for the whole group, between groups and differences in fatigue development between groups were evaluated using 2-way repeated measures ANOVA. Results: As a result of fatigue, the group (n=16) showed less ScapPostTilt (Mean=5, 5°, SD=6, 3°, p=0.004), ScapUpRot (Mean=3, 7°, SD=4°, p=0, 003), and less ScapRetr (Mean=2, 7°, SD=4°, p=0, 044), and the HumExtRot increased (Mean=3, 3°, SD=5, 9°, p=0, 048). No significant differences between groups were found, however a tendency towards greater HumExtRot was observed (Mean difference=15.2°, SD=16.9°, p=0, 089), for players with NP. Conclusions: The results indicate that fatigue has a detrimental effect on scapula and gleno-humeral kinematics, which may increase the risk of non-traumatic shoulder injuries. However P-players did not respond differently to fatigue-development.